Length of business operation and its relationship with compliance behaviour of business zakat among owners of SMEs / Mohd Rahim Khamis ... [et al.] - Khamis, Mohd Rahim; Kamarudin, Mohd Faizal; Hashim, Maryam Jameelah; Muhamad Arifin, Nur Afizah (Universit Teknologi MARA Cawangan Selangor, 2018)
Length of business operation and its relationship with zakat compliance behaviour are hardly found in the literature. This is because many studies mainly discussed zakat on income compared zakat on business. Thus, this paper aims to identify the relationship between the length of business operation and compliance behaviour of business zakat among owners of SMEs through the new application namely Rasch Measurement Model. 276 questionnaires managed to be collected from SMEs and only 253 respondents fit with the Rasch Measurement Model. The statistical indicators such as Person Item Distribution Map revealed that among 253 respondents, 41.1 percent denoting the group that complies with paying business zakat and 58.9 percent denoting the group that does not comply with paying business zakat. Interestingly, this shows the length of business operation can be said as not influenced at all in compliance behaviour of business zakat among owners of SMEs. The implication of this paper provides evidence of the usefulness of Rasch Measurement Model in identifying the relationship between the length of business operation and compliance behaviour of zakat on business that has not been explored yet by other studies.